The underwater soundscape around Australia - Erbe, Christine; McCauley, Robert; Gavrilov, Alexander; Madhusudhana, Shyam Kumar; Verma, Arti (2016)
The Australian marine soundscape exhibits a diversity of sounds, which can be grouped into biophony, geophony and anthrophony based on their sources. Animals from tiny shrimp, to lobsters, fish and seals, to the largest animals on Earth, blue whales, contribute to the Australian marine biophony. Wind, rain, surf, Antarctic ice break-up and marine earthquakes make up the geophony. Ship traffic, mineral and petroleum exploration and production, construction, defence exercises and commercial fishing add to the anthrophony. While underwater recorders have become affordable mainstream equipment, precise sound recording and analysis remain an art. Australia’s Integrated Marine Observing System (IMOS) consists of a network of oceanographic and remote sensors, including passive acoustic listening stations managed by the Centre for Marine Science & Technology, Curtin University, Perth. All of the acoustic recordings are freely available online. Long-term records up to a decade exist at some sites. The recordings provide an exciting window into the underwater world. We present examples of soundscapes from around Australia and discuss various aspects of soundscape recording, analysis and reporting—the to-dos and not-to-dos.